2012
DOI: 10.1186/1471-244x-12-28
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal expressions among young people in Nicaragua and Cambodia: a cross-cultural study

Abstract: BackgroundWhereas prevalence of suicidal expressions among young people is fairly similar in different countries, less is known about associated risk factors. This study compares young people in Nicaragua and Cambodia to examine if the pattern of association between mental health problems and suicidal expressions differs.Methods368 and 316 secondary school students, from each country respectively, participated. Self-reported suicidal expressions, exposure to suicidal behavior in significant others and mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
(42 reference statements)
1
11
0
1
Order By: Relevance
“…Another study undertaken by McKinnon et al 6 with 164,770 adolescents from 32 countries reported a prevalence rate of 16.2% and 12.2% for men and women, respectively, showing that the gender difference was more accentuated in the Americas (20.1% and 11.4%) and that African countries showed the highest prevalence of suicidal ideation (22.5% and 20.1%, respectively). Other studies conducted with adolescents have shown similar prevalence rates to those reported above [14][15][16][17][18][19][20] .…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Another study undertaken by McKinnon et al 6 with 164,770 adolescents from 32 countries reported a prevalence rate of 16.2% and 12.2% for men and women, respectively, showing that the gender difference was more accentuated in the Americas (20.1% and 11.4%) and that African countries showed the highest prevalence of suicidal ideation (22.5% and 20.1%, respectively). Other studies conducted with adolescents have shown similar prevalence rates to those reported above [14][15][16][17][18][19][20] .…”
Section: Introductionsupporting
confidence: 82%
“…These findings are in line with other investigations, including a study undertaken with schoolchildren aged between 12 and 16 years in the United Kingdon 49 and another conducted by Souza et al 14 However, other studies involving adolescents have reported weaker associations between both variables, including an investigation carried out by Kaess et al 16 in Germany [OR = 1.298; 1.259 to 1.338, CI 95%], another undertaken by Glashouwer 15 in Holland [OR = 1.95; 1.72 to 2.22, CI 95%], and a study conducted by Shilubane et al 20 in South Africa [OR = 1.755]. Two studies in Asia also confirmed this association: a study conducted by Medina et al 17 in Cambodia [OR of 1.328 and 1.164 for women and men, respectively] and another undertaken by Nguyen et al 19 in Vietnam [OR = 3.45; 2.63 to 4.54;, CI 95%,); while in Central America, Medina et al 17 obtained an OR of 1.275 and 1.650 for women and men, respectively, in a study with students aged between 15 and 18 years in Nicaragua.…”
Section: Discussionmentioning
confidence: 83%
“…Presence of positive social environment, such as social support, is likely to render social buffer against such suicidal tendencies (personal data) [8]. Another recent survey has also shown that Cambodians are less likely to be at the risk of suicidal expressions than other populations [41] [42]. Our population is rural that often has close neighborhoods; it would be difficult for someone to hide such suicidal attempts, if any, in such a “visible” environment.…”
Section: Discussionmentioning
confidence: 90%
“…It consists of 112 items that were rated as 0 = not true, 1 = somewhat true, and 2 = often true. YSR has been used in previous youth studies in different countries (24, 25) including Cambodia (26,27). The cut-off score of YSR has not been validated in Cambodia and therefore, the mean score was considered.…”
Section: Methodsmentioning
confidence: 99%